2019
DOI: 10.1158/1535-7163.mct-18-1045
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of Histologically and Molecularly Stable Soft-tissue Sarcoma Xenograft Models for Biological Studies and Preclinical Drug Testing

Abstract: Soft-tissue sarcomas (STS) represent a heterogeneous group of rare, malignant tumors of mesenchymal origin. Reliable in vivo sarcoma research models are scarce. We aimed to establish and characterize histologically and molecularly stable patient-derived xenograft (PDX) models from a broad variety of STS subtypes. A total of 188 fresh tumor samples from consenting patients with localized or advanced STS were transplanted subcutaneously in NMRI-nu/nu-immunodeficient mice. Once tumor growth was observed, the mate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
0
27
1
Order By: Relevance
“…The present study showed that the safety and antitumor efficacy of 3Pt was superior to that of CDDP in a CDDPresistant osteosarcoma PDOX model. PDOX models (12,(26)(27)(28) have important advantages over subcutaneous models (29) in that the tumors are growing in the proper microenvironment as in the present case in the bone.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the safety and antitumor efficacy of 3Pt was superior to that of CDDP in a CDDPresistant osteosarcoma PDOX model. PDOX models (12,(26)(27)(28) have important advantages over subcutaneous models (29) in that the tumors are growing in the proper microenvironment as in the present case in the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Absolute tumor volumes within groups at start and end of experiment were compared using the Wilcoxon matched-pairs signed rank test to assess tumor volume evolution. Two tumors engrafted on the same mouse were regarded as independent entities, as was demonstrated previously by our group and were thus analyzed separately [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, it should be advised that one recent study has reported that PDX models of varied tumor types develop mutations with serial passages that diverge from those observed in the patients 35. Recently, 5 PDX models were successfully established from surgical specimens and biopsies of 31 DDL patients 36. The tumors fragments were implanted bilaterally into the subcutaneous space of immunodeficient mice.…”
Section: Xenograft Models Of Liposarcomamentioning
confidence: 99%
“…Bilateral tumor engraftment and cryopreservation approaches of PDX models were used to reduce the number of mice required over time. Cryopreserved PDX tumors were successfully re-engrafted in mice 36. Such strategies are not avoid of limitations, including the need of a sufficient amount of fresh tumor tissue, the time of propagation and the failure rate of about 20% of the tumor implantation that, however, may predict lower aggressiveness.…”
Section: Xenograft Models Of Liposarcomamentioning
confidence: 99%
See 1 more Smart Citation